Search for the associated production of the Higgs boson and a vector boson in proton-proton collisions at √s = 13 TeV via Higgs boson decays to τ leptons - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2019)
A search for the standard model Higgs boson produced in association with a W or a Z boson and decaying to a pair of τ leptons is performed. A data sample of proton-proton collisions collected at √ s = 13 TeV by the CMS experiment at the CERN LHC is used, corresponding to an integrated luminosity of 35.9 fb−1 . The signal strength is measured relative to the expectation for the standard model Higgs boson, yielding µ = 2.5 +1.4 −1.3 . These results are combined with earlier CMS measurements targeting Higgs boson decays to a pair of τ leptons, performed with the same data set in the gluon fusion and vector boson fusion production modes. The combined signal strength is µ = 1.24+0.29 −0.27 (1.00+0.24 −0.23 expected), and the observed significance is 5.5 standard deviations (4.8 expected) for a Higgs boson mass of 125 GeV.